Perception and Awareness of Marine Plastic Pollution in Selected Tourism Beaches of Barobo, Surigao del Sur, Philippines - INOCENTE, Sherley Ann T.; GUTIERREZ, Carlo S.; SISON, Maria Pia M.; MADARCOS, John Roderick V.; REQUIRON, Judea Christine M.; PACILAN, Christine Joy M.; GABOY, Shiela Mae M.; SEGOVIA, Jayson Leigh M.; BACOSA, Hernando P. (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).18, 2023)
Tourism is a significant economic activity in coastal communities, but when badly managed, it degrades the health of the marine-coastal ecosystem, increasing litter pollution and repels beach visitors. This study aims to assess the tourism impact on litter pollution on four growing tourism beaches of Barobo, Surigao del Sur, Philippines. Plastic litters were sampled from four tourism sites (Cabgan Island, Turtle Island, Dapdap Beach, Panaraga Beach) of Barobo by establishing transect lines with quadrats. Those who agreed to participate in perception and knowledge tests about marine debris were interviewed at the aforementioned beaches. Respondents was generally aware of marine pollution problems, specifically marine pollution relating to human and ecological health. Respondents identified tourism as a main litter source and plastic packaging as the most common litter type, which is true based on macrolitter collection. Because tourism causes plastic pollution on all of the beaches studied, stronger regulations, educational, and awareness efforts are crucial to reduce litter pollution and avert ecological and socioeconomic consequences. Structured Abstract: Purpose : Tourism plays a big role in the economic status of a country. It provides livelihood to the community and helps in poverty elevation. But tourism also brings pollution, i.e. , plastic pollution, if not properly managed. The primary objective of this study is to evaluate the perception and awareness of tourists on plastic pollution and its impacts on tourism. Design/methodology/approach : The study was limited to surveys and key informant interviews (KII) since fora and assemblies are not allowed due to pandemic health protocols. Survey sampling was done simultaneously with the macroplastic collection from July 10 to August 12, 2021. Convenience sampling design was used, and data was collected on willing individuals present in the area. The awareness questionnaire used the Likert Scale method, while the individual perception used multiple choice or open-ended questions. Statistical data analysis was performed using SPSS and Microsoft excel. Findings : A total of 105 willing individuals were legally part of this study. Of the 105 respondents surveyed, 70 of which are tourists from island beaches and 35 are from mainland beaches. Respondents were generally aware of most issues presented to them. The top issues that the respondents relate the most are related to plastic effects on health and environment. The majority of the surveyed tourists on island beaches perceived high macrolitter pollution, while those on mainland beaches perceived low pollution. This perception of respondents agrees with the litter quantities registered and collected. Furthermore, the perception of plastic packaging as the most common type of litter has been found out to be true based on sampling collections. Tourists on the beaches of Barobo are aware of the problem of marine litter and see the tourism sector as a source of waste, notably plastics. Originality : This research paper submitted by us is an outcome of our independent and original work. We have duly acknowledged all the sources from which the ideas and extracts have been taken. The paper is free from any plagiarism and has not been submitted elsewhere for publication.